2019
DOI: 10.1111/jir.12595
|View full text |Cite
|
Sign up to set email alerts
|

The association of life events and mental ill health in older adults with intellectual disability: results of the wave 3 Intellectual Disability Supplement to The Irish Longitudinal Study on Ageing

Abstract: Background Exposures to life events are associated with emotional, psychological and behavioural problems in those with intellectual disability (ID). Older adults with ID may experience different life events given differences in living circumstances, cognitive decline, greater dependency on others and less autonomy. This study examines the relationship of life events and mental ill health in an older ID population in Ireland. Methods The study was part of ‘The Intellectual Disability Supplement to The Irish Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 25 publications
0
27
0
3
Order By: Relevance
“…Interviews were a mix of self‐report and proxy interviews completed by family and/or staff members and were administered by a trained interviewer in a location of the participant's choice, usually their home or day service centre (Bond et al . 2019).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interviews were a mix of self‐report and proxy interviews completed by family and/or staff members and were administered by a trained interviewer in a location of the participant's choice, usually their home or day service centre (Bond et al . 2019).…”
Section: Methodsmentioning
confidence: 99%
“…It was not possible to definitively conclude that anti‐epileptic medication was indicated for mood stabilisation as opposed to seizure control in participants with a diagnosis of epilepsy (Bond et al . 2019). We therefore excluded these participants ( n = 31) from the analyses. Anxiolytics (N05B) excluding rectal diazepam and Clobazam as they are used primarily for epilepsy as opposed to anxiety disorders Sedatives and hypnotics (N05C) excluding midazolam as its primary use is for acute seizure control as oppose to mental health conditions…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Albeit of these divergent figures, psychiatric disorders are more prevalent among adults with ID than in the adult general population [8,9]. An increased life expectancy among people with ID [10,11], together with a positive association between age and psychiatric disorders in this group [1,[12][13][14], results in an increasing number of older people with ID and concurrent psychiatric disorders. Research regarding psychiatric health care utilization among older people with ID is scarce [15], however, and the present study addresses this knowledge gap.…”
Section: Introductionmentioning
confidence: 99%
“…Bond et al . () report on the association between life events and mental ill health in older adults with intellectual disability, using longitudinal data from the Intellectual Disability Supplement to the Irish Longitudinal Study on Ageing (IDS‐TILDA). They found that experiencing more life events was significantly associated with the development of new psychiatric problems, as well as the initiation and increased dosage of psychotropic medications, suggesting that interventions to reduce an excess of life events in older adults with ID (e.g.…”
mentioning
confidence: 99%